Psychological Dynamics in Incarcerated Amphetamine Dependence: An Interpretive Case Study - Putu Diana Wulandari; Aritya Widianti; Ratih Saraswaty; Ni Made Irene Novianti Astaningtias (PT BMW Journal Sejahtera, 2025)
Introduction: Substance dependence among inmates presents complex psychological challenges often rooted in personal history and environmental factors. This study aims to identify and analyze the specific psychological dynamics of an inmate diagnosed with amphetamine dependence to provide a basis for effective intervention. Case Description: This study utilized a qualitative case study approach involving